2017
DOI: 10.1523/jneurosci.0659-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Serotonin Brain Mechanisms in the Nonhuman Primate

Abstract: Oxytocin (OT) is increasingly studied for its therapeutic potential in psychiatric disorders, which are associated with the deregulation of several neurotransmission systems. Studies in rodents demonstrated that the interaction between OT and serotonin (5-HT) is critical for several aspects of social behavior. Using PET scan in humans, we have recently found that 5-HT 1A receptor (5-HT 1A R) function is modified after intranasal oxytocin intake. However, the underlying mechanism between OT and 5-HT remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 55 publications
(8 reference statements)
1
40
0
Order By: Relevance
“…Mottolese and colleagues also found that administering OT, compared to a placebo, increases serotonin binding potential in regions associated with social processing, attention, and valuation in humans: DRN, amygdala/hippocampal complex, insula, and orbitofrontal cortex (Mottolese, Redouté, Costes, Le Bars, & Sirigu, ). This relationship is also present in the macaque brain (Lefevre et al, ). However, the recruitment of 5‐HT by OT seems to be heavily blunted in individuals with Autism Spectrum Disorders, suggesting that the interaction between OT and 5‐HT is crucial for typical social behaviors, including monitoring others (Lefevre et al, ).…”
Section: Introductionmentioning
confidence: 66%
“…Mottolese and colleagues also found that administering OT, compared to a placebo, increases serotonin binding potential in regions associated with social processing, attention, and valuation in humans: DRN, amygdala/hippocampal complex, insula, and orbitofrontal cortex (Mottolese, Redouté, Costes, Le Bars, & Sirigu, ). This relationship is also present in the macaque brain (Lefevre et al, ). However, the recruitment of 5‐HT by OT seems to be heavily blunted in individuals with Autism Spectrum Disorders, suggesting that the interaction between OT and 5‐HT is crucial for typical social behaviors, including monitoring others (Lefevre et al, ).…”
Section: Introductionmentioning
confidence: 66%
“…Whereas initial data suggests that ATD may reduce peripheral OXT levels in the absence of behavioral effects [80], the combination of ATD with placebo nasal spray did not produce effects on amygdala reactivity in the present study arguing against an ATD-induced unspecific decrease in OXT signaling. On the other hand, molecular imaging studies have demonstrated that intranasal OXT induces central serotonin release [9,23] and ATD leads to stable and selective reductions in central 5-HT signaling [53], including attenuation of stimulated serotonin release [53,81,82] and availability of serotonin in presynaptic neurons [83]. This suggests that pretreatment with ATD diminished OXTinduced serotonin release via OXT-sensitive receptors on serotonergic raphe neurons in which in turn attenuated anxiolytic effects mediated by serotonergic raphe-amygdala pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Overarching conceptualizations of the role of OXT in human social-emotional behavior have proposed that the complex behavioral effects of OXT are partly mediated by interactions with other neurotransmitter systems [5,6]. Such interactions have been evidenced by initial animal models demonstrating that OXT's effects in the domains of pair bonding are partly mediated by dopamine [7] whereas social reward and anxiolytic effects involve interactions with the serotonin (5-HT) system [8][9][10][11]. Previous research in rodents, non-human primates and humans has demonstrated a pivotal role of attenuated amygdala threat reactivity in mediating the anxiolytic actions of both OXT and 5-HT systems [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with the comparatively large body of medical and psychological literature on the role of serotonin on human mental health (Olivier, ). Interestingly, some recent studies have revealed the existence of an interplay between 5‐HT and OXT, and its role in social behaviour in primates (Baran, ; Lefevre et al ., ). Furthermore, some authors have shown that the administration of a serotonin receptor (HTR1A) agonist inhibits affiliative behaviour directed at the pair‐mate in social monogamous Callicebus cupreus males (Larke et al ., ) and promotes social rejection in female marmosets ( Callithrix jacchus; Aubert et al ., ).…”
Section: Introductionmentioning
confidence: 97%